Prices, Product Differentiation, and Heterogeneous Search Costs - José L. Moraga-González; Zsolt Sándor; Matthijs R. Wildenbeest (Tinbergen Institute, 2014)
We study price formation in the standard model of consumer search for differentiated products but allow for search cost heterogeneity. In doing so, we dispense with the usual assumption that all consumers search at least once in equilibrium. This allows us to analyze the manner in which prices affect the decision to search rather than to not search at all, which is an important but often neglected aspect of the price mechanism. Recognizing the role the equilibrium price plays in consumers' participation decisions turns out to be critical for understanding how search costs affect market power. This is because the two margins that determine prices|the intensive search margin, or search intensity, and the extensive search margin, or search participation|may be affected in opposing directions by a change in search costs. When search costs go up, fewer consumers decide to search, which modifies the search composition of demand such that demand can become more elastic. At the same time, the consumers who choose to search reduce their search intensity, which makes demand less elastic. Whether the effect on the extensive or the intensive search margin dominates depends on the range and shape of the search cost density. We identify conditions for higher search costs to result in higher, constant, or lower prices. Similar results are obtained when the marginal gains from search vary across consumers.
Keywords: D43; D83; L13; 330; sequential search; search cost heterogeneity; differentiated products; existence and uniqueness of equilibrium